Vitamin D supplementation improves foot ulcers among diabetic patients: Pooled analysis of randomized controlled trials - Putra, Muhammad IA.; Gusti , Naufal; Duta, Teuku F.; Alina, Meulu; Qanita, Intan; Naufal, Muhammad A.; Henira, Najlaika; Tsurayya, Ghina; Amirah, Shakira (Narra X, 2023)
Serum vitamin D level is associated with the development of diabetic foot ulcer (DFU), and it is intriguing to determine if the vitamin supplementation could reverse the diabetic complication. The aim of this study was to investigate the efficacy of vitamin D supplementation in DFU management through qualitative and quantitative systematic review. A systematic search was conducted to screen the records identified in PubMed, Scopus, Embase, Scillit, Sci-Finder, LILACS, EuropePMC, medRxiv, bioRvix, Google Scholar, Semantic Scholar, and Garuda databases as of 10 March 2023. Studies investigating the efficacy of a single dose supplementation of vitamin D in DFU management were included. Quality of the included studies was appraised by Cochrane ‘Risk of Bias’ 2.0. Random-effects-based pooled analysis using Cohen’s d was performed on the wound healing progress as the primary outcome. A sensitivity test with leave-one-out method and meta-regression were also conducted to analyze the effect of heterogenous data. Five studies with a total of 245 patients (123 versus 122 for experimental and control groups, respectively) were finally included in the qualitative and quantitative analysis. The pooled estimate suggested that administering vitamin D to DFU patients could reduce the wound area or depth significantly as compared to control group (p<0.001; Cohen’s d: 2.72; 95% CI: 1.02 to 4.42). The value remained positive throughout the leave-one-out analysis. Vitamin D supplementation significantly contributed to the increased level of serum vitamin D (p=0.026, Cohen’s d: -0.719; 95% CI: -1.35 to -0.09). Elevation of high-density lipoprotein was observed in pooled estimate with p=0.016 and Cohen’d: 1.34 (95% CI: 0.25 to 2.44). Qualitatively, significant reduction of HbA1C, total cholesterol, and C-reactive protein were reported in at least two trials. Significantly improved quantitative insulin sensitivity check index (QUICKI) and decreased malondialdehyde, fructosamine, and fasting blood glucose were reported in at least one trial each. There were conflicting results on the change of low-density lipoprotein level. This study highlights that vitamin D supplementation promotes wound healing process among DFU patients; however, it is too premature to draw solid conclusions as the efficacy could be affected by multiple factors. Therefore, clinical trials from various demographics and ethnicities by using a high- versus low-dose model are needed.